Enabling the Disabled: Negotiation of Beauty in a Disabled Model Instagram Account - Putri, Raselly Elfa; Putra, Gesang M N (Universitas Airlangga, 2024)
DEI (diversity, equity, and inclusivity) in the beauty industry is evident through the increasing number of disabled models. Working from the concept of Wolf’s Beauty Myth, this study aims to reveal how Jillian Mercado portrays and negotiates beauty through her Instagram account. The data from Mercado’s Instagram posts are analyzed semiotically to find out how beauty is negotiated by a disabled model. The result of this study found that the beauty ideal portrayed by Mercado is a negotiation of the prevailing beauty standards. Such negotiation is exemplified through her portrayal as both an individual with a disability and as a disabled model. Moreover, this study also finds that negotiation, instead of an outright rejection, of beauty standards is a conscious effort to gain acceptance and acknowledgement, a starting point to empowerment.